Identification of Pathogenic Bacteria in Cyprinus carpio Reared in Floating Cages - Erikson Sahala Pardamean; Henni Syawal; Morina Riauwaty (Jurnal Perikanan dan Kelautan, 2021)
Pathogenic bacteria is disease causing microorganisms that can attack fish and can cause mass death in cultured fish. The purpose of this study was to identify the types of pathogenic bacteria Cyprinus carpio that were reared in floating cages. This study used a survey method that is purposive sampling and the fish sample were obtained from, PLTA Koto Panjang. the fishes were identified in the Fish Parasite and Disease Laboratory, Fish and Marine Faculty, University of Riau. Fish samples used were 15-20 cm goldfish totaling 12 tails with 3 times taken from 4 different cages. The kidneys organ were examined and to find out the type the bacteria. Result shown identified of pathogenic bacteria consist of 3 types of bacteria namely Aeromonas sp., Pseudomonas sp., and Edwardsiella sp. Water quality during the study was Temperature: 27-300C, pH 6-7, DO 3.67-4.28 ppm, and ammonia 0.048-0.64 mg/L.